Full characterization of the third-order nonlinear susceptibility using a single-beam coherent anti-Stokes Raman scattering setup - Wipfler, Alexander; Rehbinder, Jean; Buckup, Tiago; Motzkus, Marcus (Optics letters, 2012)
A method for the full determination of the third-order nonlinear coherent anti-Stokes Raman scattering (CARS) susceptibility is presented, which relies on phase control of a single ultrabroadband femtosecond laser pulse. A narrowband phase gate is scanned to perform double quadrature spectral interferometry, which reveals amplitude and phase of a multiplex CARS field. A single calibration measurement in a nonresonant sample allows for the characterization of the susceptibility in amplitude and phase. This scheme is demonstrated experimentally for the fingerprint region of toluene.